PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN WAJIB PAJAK KENDARAAN BERMOTOR PADA SAMSAT DRIVE THRU MATARAM UPTD PELAYANAN PAJAK DAERAH DAN RETRIBUSI DAERAH (PPDRD) MATARAM - Ervan Anwar (Master of Management, Mataram University, 2016)
The aim of this study is to identify the effect of service quality which covers services system and procedure, personnel skill and ability, and service facilities and infrastructure on the satisfaction of motor vehicle taxpayers. This research adopts the associative research design as research guidelines. Probability sampling with simple random sampling technique were used in distributing 100 copies of questionnaire provided to taxpayers who use the service of Mataram Drive Thru. 100 copies of distributed questionnaire were entirely completed and returned to the researcher. Pearson correlation product moment were given to 100 respondents / taxpayer motorists who use services Mataram Drive Thru, 100 copies of questionnaires distributed, fully completed and returned to the researcher. Pearson Product Moment Correlation was used to analyze the data obtained from the respondents. The research findings indicate that systems and procedures of services, personil skills and ability, and service facilities and infrastructure have significant effect on the level of customers satisfaction 0,05 (2-sided). Therefore, it can be concluded that those three variables significantly affect the customers satisfaction. Further, service facilities and infrastructure was on the top rank, personil skill and abilitywas on the second, and systems and procedures was on the third. Finally, it is expected that the result of this study will help stakeholders of Mataram UPTD PPDRD office (the office of area tax service and levies) understand and identify the rank of variables influencing motor vehicle taxpayers satisfaction. Keywords: Service Qualites, Service Systems and Procedures, Personnel Skill and Abilities, Service Facilities and Infrastructure, Customers Satisfaction.